The nature of narrative - Scholes, Robert (Oxford Oxford University Press, 2006)
For the past forty years The Nature of Narrative has been a seminal work for literary students, teachers, writers, and scholars. Countering the tendency to view the novel as the paradigm case of literary narrative, authors Robert Scholes and Robert Kellogg in the original edition offered a compelling history of the genre narrative from antiquity to the twentieth-century, even as they carried out their main task of describing and analyzing the nature of narrative's main elements: meaning, character, plot, and point of view. Their history emphasized the broad sweep of literary narrative from ancient times to the contemporary period, and it included a chapter on the oral heritage of written narrative and an appendix on the interior monologue in ancient texts.
Includes bibliographical references (p. 373-377) and index.
Keywords: Fiction--History and criticism